Analisis Likuiditas, Solvabilitas, Kebijakan Deviden, dan Inflasi dengan Profitabilitas Sebagai Variabel Intervening Terhadap Price To Book Value (Studi Kasus pada Perusahaan Asuransi yang Tercatat di Bursa Efek Indonesia Periode 2016-2021) - Jesica Virdayanti; Suyanto Suyanto; Novita Manda Sari Tanjung (J-MAS (Jurnal Manajemen dan Sains), 2022)
The reason for investors to invest in companies is because the company has good performance and low risk, with the good performance is expected to increase the wealth of investors. This can be done by applying various alternative ways of assessing whether the company, especially the selected insurance company, is a company that will provide benefits in the future through fundamental analysis, technical analysis, investment appraisal, or company performance. Liquidity, Solvency, Dividend Policy, Profitability, and Inflation are one of the investment assessments used to invest in the company. This study aims to determine the effect of liquidity, solvency, dividend policy, profitability, and inflation on firm value in the insurance sector listed on the Indonesia Stock Exchange from 2016-2021. The population in this study is an insurance sector company listed on the Indonesia Stock Exchange (IDX) during the 2016-2021 observation period. The sample selection uses documentation data techniques (desk research). The number of samples obtained from 9 companies. This study uses secondary data obtained from the company's financial statements obtained through the IDX's official website www.idx.co.id which was analyzed by descriptive statistical methods with analytical methods: SEM - Partial Least Square (PLS) with a t statistic of 1.65 and p values 0.10 with a significance level of 10%. The results show that liquidity has a significant effect on profitability, liquidity has a significant effect on the price to book value, solvency has a significant effect on profitability, solvency does not affect the price to book value, dividend policy has no effect on profitability, dividend policy has no effect on the price to book value. , inflation does not affect profitability, inflation has no effect on the price to book value, profitability has no effect on the price to book value, liquidity does not affect the price to book value through profitability, solvency does not affect firm value through profitability, dividend policy does not affect the price to book value. book value through profitability, inflation does not affect the price to book value through profitability.